2016
DOI: 10.1111/his.13098
|View full text |Cite
|
Sign up to set email alerts
|

Modern therapies and iatrogenic changes in breast pathology

Abstract: Iatrogenic changes within the breast can provide challenges for the histopathologist in routine practice. Diagnostic procedures, such as core biopsies, result in reactive changes and can cause displacement of benign and malignant cells, the interpretation of which may cause difficulties in the resection specimen. Breast augmentation surgery with implants or injection of fillers, performed for cosmetic reasons or as part of a reconstructive process following removal of breast cancer, also produces reactive chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 110 publications
0
24
0
Order By: Relevance
“…In rare cases, recurrence adenosquamous carcinoma of breast is invasive ductal carcinoma with ER and PR expression, [ 12 ] it could be that adjuvant chemotherapy alters the hormone receptor status. [ 13 ] In addition, it was reported that hormone receptors can regulate the expression of CD44v, which is considered having correlation with cellular differentiation in breast cancer. [ 14 ] The expression of CD44v is mainly restricted to myoepithelial cells in normal breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, recurrence adenosquamous carcinoma of breast is invasive ductal carcinoma with ER and PR expression, [ 12 ] it could be that adjuvant chemotherapy alters the hormone receptor status. [ 13 ] In addition, it was reported that hormone receptors can regulate the expression of CD44v, which is considered having correlation with cellular differentiation in breast cancer. [ 14 ] The expression of CD44v is mainly restricted to myoepithelial cells in normal breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although BIA-ALCL is of T-cell lineage, the neoplastic cells are usually negative for CD7 and often lack other pan-T-cell antigens, such as CD2, CD3, and CD5. 23,71 The B-cell markers CD20 and CD79a and the plasma-cell marker CD138 are negative. Unlike a subset of systemic ALCL, BIA-ALCL is consistently Alk-1 negative.…”
Section: Histopathologymentioning
confidence: 99%
“…Some neoplastic cells may resemble the "hallmark" cells described in systemic anaplastic large cell lymphoma (ALCL), which have kidney-shaped nuclei and paranuclear eosinophilia on hematoxylin-eosin-stained sections. 71 Neoplastic cells can be present individually in aspirated fluid, as small nests within fibrinoid and necrotic material adherent to the inner surface of a capsule or as sheets within a mass lesion. 19,25,72 Often there is an associated inflammatory cell infiltrate, including small lymphocytes, histiocytes, and eosinophils.…”
Section: Histopathologymentioning
confidence: 99%
“…Several types of antitumor agents, including hormone therapy, chemotherapy, and radiotherapy have been investigated in preclinical research ( 21 , 22 , 24 28 ), and a safety and feasibility clinical trial was successfully conducted with Doxil administered by the i.duc route ( 22 ). The results are promising overall, but problems still exist, such as suboptimal antitumor efficiency of endocrine agents ( 26 ) and long-term effects of DNA-damaging agents such as chemotherapy and radiotherapy ( 49 ). Treatment using biological agents such as antibodies or antibody-targeted protein toxins may circumvent these problems.…”
Section: Discussionmentioning
confidence: 99%